2010
DOI: 10.1016/j.foodchem.2009.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and evaluation of radical scavenging peptides from in vitro digests of buckwheat protein

Abstract: Buckwheat protein (BWP) isolate was subjected to a two-stage in vitro digestion (1 h pepsin followed by 2 h pancreatin at 37 °C). The antioxidant potential of the BWP digests was compared by assessing their capacity to scavenge 2,2′-azinobis (3-ethylbenzothiszoline-6-sulphonic acid) (ABTS +• ) and hydroxyl ( • OH) radicals. The 2-h pancreatin digest, which demonstrated the strongest activity against both radicals, was subjected to Sephadex G-25 gel filtration. Of the six fractions collected, fractions IV (456 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 25 publications
7
68
0
Order By: Relevance
“…•+ or DPPH • [Ma et al, 2010;Alashi et al, 2014]. Results of our study are consistent with this observation.…”
Section: And Dpphsupporting
confidence: 92%
See 1 more Smart Citation
“…•+ or DPPH • [Ma et al, 2010;Alashi et al, 2014]. Results of our study are consistent with this observation.…”
Section: And Dpphsupporting
confidence: 92%
“…•+ scavenging activity of buckwheat proteins digested with the same system of enzymes was increasing in the course of hydrolysis [Ma et al, 2010]. A few studies demonstrated that fractions of peptides with the lowest MW separated from pancreatin hydrolysates were characterised by a high antiradical activity against ABTS…”
Section: And Dpphmentioning
confidence: 99%
“…Various peptides derived from animal or plant proteins were reported to exhibit radical-scavenging activity in food and biological systems (Ma, Xiong, Zhai, Zhu, & Dziubla, 2010;Rao et al, 2012;Shen, Chahal, Majumder, You, & Wu, 2010;Xia, Bamdad, Gänzle, & Chen, 2012;Zhang, Mu, & Sun, 2014). One of the most widely used assays to screen anti-radical peptides is the ABTS assay.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some researchers illustrated that peptides containing histidine as the second N-terminal residue in the sequence possessed particularly strong antioxidant activity [33]. Some amino acids rich in bioactive peptide such as cysteine, serine, proline, lysine, leucine (isoleucine) tryptophane, valine have been reported with pretty good antioxidant capacity [16, 26, [16], LARL, LHY obtained from sardinelle by-product hydrolysate [35] and WPL, VPW and VFPW released from buckwheat protein [36] all have strong radical scavenging and antioxidant activity. Contrary to those findings, only one of the peptides (EHLREKVL) isolated from AHA in the present study contains histidine, but all of the seven peptides contain lysine.…”
Section: Purification and Identification Of Antioxidative Peptidesmentioning
confidence: 99%